Investigating the Effect of Muscular Relaxation Technique on Sleep Quality in Children with Leukemia Treated with Chemotherapy in Educational Hospitals of Zahedan - Zeinab Poodineh (Journal of Global Pharma Technology, 2017)
Introduction and objective: Sleep has long been considered as an important factor in human health. Sleepless clinically causes stress and the inability in performing social and job functions and it leaves considerable negative effect on quality of life and health status of people. Therefore, this study was conducted to determine the effect of muscular relaxation technique on sleep quality of parents of children with leukemia treated with chemotherapy.Methods this study is a randomized controlled intervention study in which 120 parents of children with leukemia were assigned in two groups of intervention and control. The intervention group received Benson's relaxation technique. Data collection tool included demographic information questionnaire and Pittsburgh Sleep Quality Index (PSQI). Data were analyzed by SPSS version 18 software, Paired Samples t-test, Wilcox on test, and t-test tests, Pearson correlation test, and One - Way ANOVA test.Results The mean score in the intervention group before and after intervention in the sleep quality was obtained 13.5 ± 60.5 and 5.7 ± 3.43, respectively, and significant difference was found between the quality of sleep in the two groups of intervention and control after intervention, and the relationship between quality of sleep of parents, education, gender, and their living place was not statistically significant.Conclusion The findings indicate that presence at hospital to care for the child could affect the sleep quality, because it disturbs the normal life conditions of the person. To improve their sleep status, is better that health care and management and personnel to take necessary steps to improve the quality of their sleep.Keywords: Muscular relaxation, Sleep quality, Leukemia, chemotherapy.